SOME NEW INTEGRAL INEQUALITIES FOR ρ–CONVEX FUNCTIONS - Kashuri, Artion; Aamir Ali, Muhammad; Abbas, Mujahid (Matematichki Bilten, 2020)
The aim of this paper is to generalize the results in [10] using the class of \(ρ\)-convex functions. Some special cases are deduced from main results. Applying our ideas and techniques, new interesting inequalities can be obtained in a similar way for different class of functions and operators.